EFEKTIFITAS KETRAMPILAN MENULIS BAHASA JERMAN BERBASIS DARING DI SMAN 1 TARIK KELAS X - Maharani, Deby Vista; Pujosusanto, Ari (LATERNE, 2021)
This study aims to determine the level of understanding of students for German writing skills using online learning methods. This research was conducted at SMAN 1 Tarik, class X IBB, with a total of 32 students. This research is included in descriptive quantitative research where the results of the data from this study are in the form of values and answers to questionnaires that have been given to students and then described. The instrument of this study used two methods, namely questionnaires and test questions with the Kennenlernen theme. This questionnaire will be distributed via Google Form while the test questions will be distributed via Google Classroom. The data from the test and questionnaire answers were then analyzed using the KKM value formula and the Likert scale. This research was conducted in two meetings. The first meeting was used to conduct teaching with the online method as well as to test test questions and to produce data from all the number of students. 69% of students scored above the KKM score set by the school while 31% of students did not take the test questions given. The second meeting was used to distribute questionnaires to students by producing data. 65.3% of students answered strongly agree, 25.4% answered agree, 6.9% answered doubt, 1.4% of students answered disagree and 0.9% students answered strongly disagree regarding learning using online methods. Based on the results of the study, it can be concluded that learning German writing skills using the online method at SMAN 1 Tarik can be said to be effective both in terms of learning outcomes and student responses. However, in practice, it still has several obstacles, such as the lack of responsiveness of students to German online learning.